2005
DOI: 10.1021/ja043083i
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Activation and Catalytic Aerobic Oxidation by a Mononuclear Nonheme Iron(II) Complex

Abstract: We have used dioxygen, not artificial oxidants such as peracids, iodosylarenes, and hydroperoxides, in the generation of a mononuclear nonheme oxoiron(IV) complex, [Fe(IV)(TMC)(O)]2+ (TMC = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane), from its corresponding Fe(II) complex, [Fe(TMC)(CF3SO3)2]. The formation of oxoiron(IV) species by activating dioxygen was markedly dependent on iron(II) complexes and solvents, and this observation was interpreted with the electronic effect of iron(II) complexes on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 24 publications
10
134
0
Order By: Relevance
“…15,21,54 Since then, a handful of non-heme iron(IV)-oxo complexes have been synthesized using macrocyclic tetradentate N4, tripodal tetradentate N4, and pentadentate N5 and N4S ligands ( Figure 3 for ligand structures). 5,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]55 The structural analysis of the intermediates by X-ray crystallography for [(TMC)Fe…”
Section: Mononuclear Non-heme Iron(iv)-oxo Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…15,21,54 Since then, a handful of non-heme iron(IV)-oxo complexes have been synthesized using macrocyclic tetradentate N4, tripodal tetradentate N4, and pentadentate N5 and N4S ligands ( Figure 3 for ligand structures). 5,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]55 The structural analysis of the intermediates by X-ray crystallography for [(TMC)Fe…”
Section: Mononuclear Non-heme Iron(iv)-oxo Complexesmentioning
confidence: 99%
“…19 While two-electron oxidation of Fe(II) to the Fe(IV)-oxo species was proposed in the reactions of single-oxygen atom donors (reaction a), 15,16 Fe(III)-OOR species was homolytically cleaved to form Fe(IV)-O species in the reactions of hydroperoxides (reaction b). 53,57 In the case of O 2 activation (reaction c), we found that the structures of iron(II) complexes and solvents (e.g., alcohols) are important factors in generating iron(IV)-oxo species by activating O 2 .…”
Section: High-valent Iron(iv)-oxo Complexes Nammentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Besides structural and spectroscopic characterization, a wealth of reactivity data is rapidly accumulating that demonstrates the versatility of these reagents, which can perform a variety of transformations: alkane oxidation, [16][17][18] alcohol oxidation, [19,20] olefin epoxidation, [17,18,21] oxygen transfer to dialkylsulfides and trialkylphosphines, [13,18,[21][22][23][24][25][26] and hydrogen abstraction from dihydroanthracene. [26][27][28] Interestingly, these complexes exhibit unusual kinetic isotope effect (KIE) patterns in H-abstraction reactions, ranging from near-classical KIE values of 10 for some reactions [26] to nonclassical values of 50-60 in others.…”
Section: (O)tmca C H T U N G T R E N N U N G (Ncch 3 )]mentioning
confidence: 99%
“…[28] A few reports describe oxygen-atom transfer reactions from dioxygen to triphenylphosphine, or oxidation of benzylic alcohols to aldehydes by using iron(II) complexes of cyclic amines, or even ironA C H T U N G T R E N N U N G (III) derivatives of tetraamido cyclic ligands, for which a m-oxodiiron(IV) species was characterized. [29,30] In these cases, the postulated metal-oxo based mechanism must at least share two common steps: 1) coordination of dioxygen to the metal center and 2) formation of potentially reactive intermediates such as peroxidic or high-valent oxoiron species that might react with substrates if present in the medium.…”
Section: Introductionmentioning
confidence: 99%